Government Spending Effects in a Policy Constrained Environment - Mao, Ruoyun (IMF Working Papers; Working Paper ;, 2020)
The theoretical literature generally finds that government spending multipliers are bigger than unity in a low interest rate environment. Using a fully nonlinear New Keynesian model, we show that such big multipliers can decrease when 1) an initial debt-to-GDP ratio is higher, 2) tax burden is higher, 3) debt maturity is longer, and 4) monetary policy is more responsive to inflation. When monetary and fiscal policy regimes can switch, policy uncertainty also reduces spending multipliers. In particular, when higher inflation induces a rising probability to switch to a regime in which monetary policy actively controls inflation and fiscal policy raises future taxes to stabilize government debt, the multipliers can fall much below unity, especially with an initial high debt ratio. Our findings help reconcile the mixed empirical evidence on government spending effects with low interest rates.